MiR-21 functions oppositely in proliferation and differentiation of neural stem/precursor cells via regulating AKT and GSK-3Î² - Gao, X.; Li, X.; Qian, C.; Li, F.; Zhang, Y.; Dang, L.; Xiao, X.; Liu, F.; Li, H.; Zhang, X. (Cellular and Molecular Biology, 2016)
MicroRNA involves in regulating behavior of neural stem/precursor cells (NSPCs), thus it offers the potential to treat central nervous system disease. However, the effect of miR-21 on NSPCs remains unknown. In this study, we demonstrated that miR-21 reduced proliferation and promoted neural differentiation in NSPCs via regulating the activation of AKT and GSK-3Î² signaling pathways in vitro. During differentiation of NSPCs, the expression of miR-21 was increased in a time-dependent manner by qRT-PCR. Synthesized pre-miR-21 or anti-miR-21 was transfected into NSPCs, thereby efficiently overexpressing or knocking down miR-21. Overexpression of miR-21 promoted the neural differentiation of NSPCs, as indicated by Tuj1 and PSA-NCAM staining. Interestingly, knocking down miR-21 had the opposite effect of neural differentiation in NSPCs. However, in proliferation area, overexpression of miR-21 decreased the cell viability by 3-((2-methyl-1,3-thiazol-4-yl)ethynyl)pyridine hydrochloride (MTT) assay, and inhibited the proliferation of NSPCs, as indicated by 5-Bromo-2-deoxyUridine (BrdU) staining. And likewise, knocking down miR-21 had the opposite effect of cell viability and proliferation. Western blot showed that overexpression of miR-21 enhanced the expression of Cyclin D1, however, knocking down miR-21 prevented its expression. Furthermore, we revealed that protein kinase B (AKT) and glycogen synthase kinase-3 beta (GSK-3Î²) signaling pathways were involved in the proliferation and neural differentiation of NSPCs. Overexpression of miR-21 activated AKT, and the p-GSK-3Î² was increased. Conversely, knocking down miR-21 blocked the activation of AKT, and decreased the phosphorylation level of GSK-3Î². These results demonstrated that miR-21 promotes neural differentiation and reduces proliferation in NSPCs via regulating AKT and GSK-3Î² pathways. These findings may help to develop strategies for treatment of central nervous system diseases.